Pengaruh Pengambilan Keputusan Nasabah Melalui Loyalitas Pada Asuransi Takaful Keluarga Sumatera Utara - Zulfa Aliyah; Nurlaila Nurlaila; Fauzi Arif Lubis (Jurnal Ilmiah Ekonomi Islam, 2022)
The decision to choose sharia insurance is a customer's behavior after consideration has been carried out by studying the conditions in choosing sharia insurance products. The purpose of this study was to determine the direct and indirect effect of product, service, promotion, and religiosity variables on customer decision making through loyalty to takaful insurance in North Sumatra. This research method uses a quantitative approach with path analysis and uses the help of the SPSS program. From the results of the significance test, the product has a significant and significant effect on customer decision making to choose family takaful insurance in North Sumatra through loyalty as an intervening variable. Service, promotion and religiosity have no significant and significant effect on customer decision making to choose family takaful insurance in North Sumatra through loyalty as an intervening variable with a 95% confidence level or an error rate of 5%